2000
DOI: 10.1006/mthe.2000.0215
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific and Regulatable Transgenesis in the Adult Brain: Adenovirus-Encoded Combined Transcriptional Targeting and Inducible Transgene Expression

Abstract: To achieve transient transgenesis within specific areas or cell populations in the adult central nervous system (CNS), we have developed a dual adenoviral vector system encoding for cell-type-specific and regulatable transcription units. To achieve combined cell-type-specific transcriptional targeting and inducible expression, we have engineered the expression of the tetracycline-dependent transcriptional elements (1) to be under the transcriptional control of either the astrocyte-specific, glial fibrillary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…Work from our laboratory has demonstrated that the GFAP promoter has restricted glial cell-type specificity; Decorin overexpression for glioma treatment A Biglari et al however, transgene expression levels are lower than the hCMV promoter, both in cell lines and in primary cultures. 36 Lower expression from the GFAP promoter could explain the failure of RAd/GFAP/decorin to improve the survival of tumor-bearing animals.…”
Section: Decorin Overexpression For Glioma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Work from our laboratory has demonstrated that the GFAP promoter has restricted glial cell-type specificity; Decorin overexpression for glioma treatment A Biglari et al however, transgene expression levels are lower than the hCMV promoter, both in cell lines and in primary cultures. 36 Lower expression from the GFAP promoter could explain the failure of RAd/GFAP/decorin to improve the survival of tumor-bearing animals.…”
Section: Decorin Overexpression For Glioma Treatmentmentioning
confidence: 99%
“…21,40 To create the shuttle vector pDE1/GFAP/decorin, which was used to generate RAd/GFAP/decorin, a blunted EcoRI human decorin fragment (1780 bp) was cloned into the blunted BamHI site of the pDE1/GFAP. 36 A blunted EcoRI human decorin fragment (1780 bp) was cloned into the blunted BamHI site of pAL119 (pMV35 in Shering et al 40 ) to create the shuttle vector pAL119/decorin which was used to generate RAd/hCMV/decorin. Recombinant adenoviruses encoding the decorin gene were then generated by homologous recombination in 293 cells following cotransfection of the shuttle vector and pJM17 plasmid (Microbix biosystems, Inc.).…”
Section: Recombinant Adenovirusesmentioning
confidence: 99%
“…Since we used identical viral doses of all vectors, the same number of neurons should be transduced by either vector. Taking into account that cell-type specific promoters are several fold less potent at driving expression of transgenes from Rads, 35,36,[48][49][50][51] the fact that RAd-hCMV-Gli1 and RAd-Ta1-Gli1 were equally effective suggests that neuronal expression of Gli1 is a very Figure 7 Neuropathology of TH-immunoreactive fibers following the injection of RAd vectors expressing GDNF into the striatum of animals subsequently injected with the neurotoxin 6-OHDA. (a) shows a larger representation of the area surrounding the needle tract in the ipsilateral striatum of an animal treated with 6 Â 10 7 IU RAd-GDNF and subsequent 6-OHDA.…”
Section: Neuronal Expression Ofmentioning
confidence: 99%
“…33,34 Gli1 is a transcription factor and is thus needed intracellularly in order to be able to exert its neuroprotective effects. Having previously demonstrated the specificity 35 and therapeutic effectiveness 36 of cell-type specific promoters within adenoviral vectors, we hypothesized that expression of Gli1 from a neuronal-specific promoter could increase its effectiveness and safety. We chose the neuronal-specific tubulin a1 (Ta1) promoter to drive expression of both the marker and potentially therapeutic transgenes.…”
Section: Introductionmentioning
confidence: 99%
“…11 These results suggest the need for improving vector efficiency and expression and minimizing the host immune response against the vector, along with better vector and GCV delivery methods. Some of these objectives might be achieved with the use of stronger 47 or cell -type -specific promoters 48 within first-generation or high -capacity /''gutless'' RAd vectors. 49 Another adenovirus currently undergoing clinical trials is ONYX -015, which is an E1B -55K -deleted adenovirus vector that selectively replicates and lyses p53-deficient cancer cells.…”
Section: Discussionmentioning
confidence: 99%